2013
DOI: 10.1111/jace.12629
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evolution and Growth Behavior of In Situ TiB Whisker Array in ZrB2SiC/Ti6Al4V Brazing Joints

Abstract: An in situ short fiber reinforced brazing technique by taking advantage of reaction between ZrB2 and Ti has been developed for joining ZrB2–SiC ceramic and Ti6Al4V alloy. The Ag–Cu eutectic alloy was used as brazing interlayer to realize controllable growth of TiB in Ti‐rich environment. The microstructural evolution of the joint was divided into four stages as experiments performed from 840°C to 920°C. The diffusion behaviors of Ti and B may play an important role on the preferential growth of TiB whiskers du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Therefore, a conjecture is presented that, given its high activity and comparatively small atomic radius, elemental C from the reduced graphene diffuses into the W crystal lattice to form WC through the sintering process. Additionally, a small amount of B from HfB 2 permeates into the W interlayer as interstitial atoms, likely to be the same atomic diffusion process as previously reported 32–34 . The good reaction bonding between W and matrix layers and the lack of microcracks minimize the negative effect of residual stresses on the mechanical properties produced by the thermal mismatch between the two components.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…Therefore, a conjecture is presented that, given its high activity and comparatively small atomic radius, elemental C from the reduced graphene diffuses into the W crystal lattice to form WC through the sintering process. Additionally, a small amount of B from HfB 2 permeates into the W interlayer as interstitial atoms, likely to be the same atomic diffusion process as previously reported 32–34 . The good reaction bonding between W and matrix layers and the lack of microcracks minimize the negative effect of residual stresses on the mechanical properties produced by the thermal mismatch between the two components.…”
Section: Resultssupporting
confidence: 51%
“…Additionally, a small amount of B from HfB 2 permeates into the W interlayer as interstitial atoms, likely to be the same atomic diffusion process as previously reported. [32][33][34] The good reaction bonding between W and matrix layers and the lack of microcracks minimize the negative effect of residual stresses on the mechanical properties produced by the thermal mismatch between the two components.…”
Section: Microstructural Characteristicsmentioning
confidence: 99%
“…19 The reinforcements can be better fabricated by the in-situ synthesis technique due to its uniform distribution and favorable cohesion between particles and matrix compared to ex-situ technique, thereby exhibiting the outstanding reinforcing effect. [20][21][22][23][24] Yang et al 13 reported that the formation of in-situ TiB whiskers and TiN particles in brazing seam led to 340% improvement in the shear strength of SiO 2 -BN/Ti joints. Song et al 25,26 also significantly improved the C/C composite/TC4 joints with TiC as reinforcements formed in situ during brazing.…”
Section: The Poor Wettability Of Most Metal On Ceramic Surfacementioning
confidence: 99%
“…Hereby, brazing has been industrially proven as a reliable and practical joining process for the manufacture of complex ceramic components. 3 Commercially available Ag-based active brazing fillers such as Cusil ABA (Ag-35.3Cu-1.75Ti, in wt.%), [4][5][6] Ticusil (Ag-26.7Cu-4.5Ti, in wt.%), 6 Incusil ABA (Ag-32.25Cu-12.5In-1.25Ti, in wt.%) 7 as well as laboratory-made Ag-Cu filler [8][9][10][11][12][13][14][15][16] have been used for brazing SiC ceramics due to their good wettability characteristics. [17][18][19][20][21] The most commonly used tests to characterize the mechanical performance of the joints are bending and shear tests.…”
Section: Introductionmentioning
confidence: 99%